Anion-coordination-driven single–double helix switching and chiroptical molecular switching based on oligoureas. Issue 17 (11th April 2022) - Li, Hongfei; Kou, Lei; Liang, Lin; Li, Boyang; Zhao, Wei; Yang, Xiao-Juan; Wu, Biao
Abstract : Two-in-one switching of single–double helical forms and helicities is demonstrated using anion-coordination-driven oligourea foldamers. Abstract : Synthetic foldamers with helical conformation are widely seen, but controllable interconversion amongst different geometries (helical structure and sense) is challenging. Here, a family of oligourea (tetra-, penta-, and hexa-) ligands bearing stereocenters at both ends are designed and shown to switch between single and double helices with concomitant inversion of helical senses upon anion coordination. The tetraurea ligand forms a right-handed single helix upon chloride anion (Cl − ) binding and is converted into a left-handed double helix when phosphate anion (PO4 3− ) is coordinated. The helical senses of the single and double helices are opposite, and the conversion is further found to be dependent on the stoichiometry of the ligand and phosphate anion. In contrast, only a single helix is formed for the hexaurea ligand with the phosphate anion. This distinction is attributed to the fact that the characteristic phosphate anion coordination geometry is satisfied by six urea moieties with twelve H-bonds. Our study revealed unusual single–double helix interconversion accompanied by unexpected chiroptical switching of helical senses.